Utilization of Corn Cob Waste as an Alternative Catalyst in Catalytic Converters for Diesel Engine Carbon Emission Reduction - Muhajir Muhamad; Imron Musthofa; Hajar Isworo; Muhammad Rezki Fitri Putra; Bayu Agung Wicaksono (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
Catalytic converters function to transform harmful exhaust gases into less hazardous substances through catalytic reactions, primarily oxidation and reduction. This study aims to investigate the potential of corncob waste as an alternative catalytic material in catalytic converters for reducing carbon emissions from diesel engines. The methodology involves synthesizing biochar-based catalysts derived from corncobs via pyrolysis, followed by performance evaluation within a catalytic converter system under varying engine speeds: 700 RPM, 900 RPM, and 1100 RPM. Experimental results demonstrate that catalytic efficiency does not increase monotonically with char content; instead, the 70% char formulation achieved the highest smoke opacity reduction, recording 18.90% at 700 RPM and 14.70% at 900 RPM, outperforming both the 50% and 100% variants at 1100 RPM, where exhaust temperature and flow rate increase substantially, the 100% char catalyst showed comparatively greater stability, achieving a reduction of 5.50%, while the 70% formulation declined to 2.90%. These quantitative outcomes confirm that optimal performance arises from a balanced char loading that maximizes reactive surface area while preserving gas–solid interaction efficiency. Corncob biochar thus represents a viable and sustainable alternative to metal-based catalysts. However, the variability in performance across operating conditions and the need for improved thermal durability underscore the importance of further material optimization for commercial diesel applications.